FOREWORD - Epure, Manuela (Journal of Economic Development, Environment and People, 2019)
Digital transformation is shaping our lives continuously. The current economic trends confirm the shift to the digital economy and society. Significant changes occurred at micro and macro levels, new financial and commercial models emerged due to the digital platforms and ecosystems. Digital platforms and ecosystems are created, managed and governed to support the private entrepreneurial initiatives. For the private sector, digital platforms come with the promise of exponential economic growth, scale through the network effects and no assets needed. Recent research shows that emerging digital ecosystems will score 60 trillion in revenue by 2025, which represents more than 30% of the global corporate revenue, and for the moment, only 3% of companies have adopted an active platform strategy....